Rancangan Sistem Informasi Penjualan pada Toko Kue - Permatasari, Angelina (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The purpose of this research is to analyze the problems that may occur in the cake stores, especially theselling system used in the store, identify information needs and designing suitable sales information systems for the store. The methodology used in this research are analysis and design methods. Analysis methods that used in this research are study literature, observation, survey of the old system, analysis of survey needs, identification of information needs and interview. While the design method that used in this research is Object Oriented Analysis and Design (OOAD). The results achieved is sales information system for cake store in the form ofapplication design to replace the manual system. Conclusion, a computerized sales information system can improve existing sales procedures and solve the problems that may occur in the old system.